2022
DOI: 10.24018/ejbmr.2022.7.4.1472
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Perceived Risk and Perceived Value on Customer Loyalty through Customer Satisfaction as Intervening Variables on Bukalapak Users

Abstract: The increase in e-commerce users is an opportunity for the marketplace to enter Indonesia. The number of marketplaces makes consumers more selective in shopping. To continue to compete, the marketplace cannot focus on getting new buyers, but must also create loyalty for existing customers. The purpose of this study is to explain the effect of perceived risk and perceived value on customer loyalty through customer satisfaction as an intervening variable. This research was conducted on 108 respondents, data was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 2 publications
(3 reference statements)
2
15
0
4
Order By: Relevance
“…The results of research from Soliha et al (2021) and Estikowati et al (2020) stated that customer satisfaction has a positive effect on loyalty, and mediates trust with customer loyalty. H4: Consumer satisfaction positively mediates consumer loyaltyThe research conducted is a modification of the research conducted byGiao et al (2020);Gloria & Achyar (2018); andKhasbulloh & Suparna (2022). The results of the modification of this study resulted in the following research model:…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The results of research from Soliha et al (2021) and Estikowati et al (2020) stated that customer satisfaction has a positive effect on loyalty, and mediates trust with customer loyalty. H4: Consumer satisfaction positively mediates consumer loyaltyThe research conducted is a modification of the research conducted byGiao et al (2020);Gloria & Achyar (2018); andKhasbulloh & Suparna (2022). The results of the modification of this study resulted in the following research model:…”
mentioning
confidence: 91%
“…This research is a modification of research conducted by Giao et al (2020), Gloria & Achyar (2018),and Khasbulloh & Suparna (2022)which are related to the effect of perceived usefulness, trust, and risk on consumer satisfaction and loyalty. This research will further examine the effect of perceived usefulness, trust, and risk on loyalty in the TikTok Shop: test consumer satisfaction as a mediating variable, where Tiktok Shop is currently a trend in society since the Covid-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study strengthen research findings (Adriani & Warmika, 2019), concluding that perceived value has a significant positive effect on customer satisfaction. Research (by Amri et al, 2019) ; (and Khasbulloh & Suparna, 2022) found that perceived value significantly positively affects customer satisfaction.…”
Section: Perceived Value Can Increase Customer Satisfactionmentioning
confidence: 99%
“…Consumers will buy and get satisfaction from companies or service providers that they think to offer the highest perceived value and are considered able to fulfil their requests and solve their problems (LinkAja users). (Khasbulloh & Suparna, 2022) Perceived value is a comparison between the perceived benefits and the costs incurred by consumers to obtain certain products or services.…”
Section: Perceived Value Can Increase Customer Satisfactionmentioning
confidence: 99%
“…Furthermore, in attracting tourists to visit a recreational area and increasing tourist visits, this can be done by providing even greater satisfaction to the visitors who come to visit. Creating customer satisfaction can provide several benefits too, company and consumer relations be harmonious, provide a good basis for repeat purchases, can encourage the creation of consumer loyalty, form word-of-mouth recommendations that benefit the company, the profit earned increases (Khasbulloh & Suparna, 2022).…”
Section: Introductionmentioning
confidence: 99%